Trashumancia, Espacio para Poesía y Arte : mayo-agosto 1994 - Ocaranza, Jorge Octavio (dirección); Orendain, Jorge (coordinación) (Trashumancia, 1994)
Contiene obra de: Lauro Zavala, José Ramos, Arturo Suárez, Alejandro Rossi, León Plascencia Ñol, Armando Chong, Jacques Prévert, Galway Kinell, Silvia Eugenia Castillero, Alejandro Ramírez Hernández, Bruno de Howard, Carlos Adolfo Gutiérrez Vidal, Diego Velasco, Enoé Eréndira, Gonzalo Isidro Bruno, Ramón Gil Olivo, Rolando Revagliatti, Adolfo Ruiseñor, Alejandro Riestra, Ambar Past, Blanca Margarita López Alegría, Efraín Bartolomé, Gustavo Ruiz Pascacio, José Falconi, Luciano Villarreal, Marisa Trejo, Rubén de Leo, Uberto Santos, Ubel Vázquez, Alejandro González, Andrés Echeverri, Angel Ortuño, Angélica Martínez, Antonio López Mijares, Arturo Chavoya, Diego Velasco, Fernando Bedolla, Gloria Velázquez, Felipe Ponce, Irving Ramírez, Javier Ramírez, Juan Manuel Roca, José Orpi, Karla Santodomingo, Liliana Quirarte, Luis Armenta Malpica, Marcela Saiffe, Marisa Salazar, Ramón Fernández-Larrea, Rodolfo Orozco, Teresa Riggen, Verónica Melgoza y Yong-Tae Min.